PENGEMBANGAN USAHA KERIPIK SINGKONG “NYAMEN” DI SUNGAILIAT - Yudi Oktriadi; Sukanto Sukanto; Achmad Afriadi (Jurnal Pengabdian Masyarakat Polmanbabel, 2022)
Snacks that are often consumed when gathering, one of which is cassava chips both with family, friends and in community activities. The process of making cassava chips is passed through several stages, namely in the form of slicing cassava into thinness then fried, dried/ drained, stirred together with flavored spices and as well as packing. From the survey that has been carried out on partners, the process of stirring cassava chip seasoning is one of the main problems because the stirring process still uses manual using plastic containers. The stirring process is carried out for 2 minutes with the amount of capacity of the chips stirred only 8 ounces and drains a lot of time. From this problem, it makes a cassava chip seasoning kneading machine that can replace human labor, so that the capacity and time can be increased. The implementation method to solve the problem provides assistance with a cassava chip seasoning mixer with a capacity of 5 kilogram which works for 10 minutes in each process, provides brief training on the operation and maintenance of the machine, and receives complaints and repairs to damage that occurs to the machine. It can be concluded that the help of a cassava chip seasoning machine to partners is very helpful in the development of the cassava chip business with faster and more practical results in the use of the machine.